2018
DOI: 10.1590/0001-3765201720170453
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes immobilized in Langmuir-Blodgett films: Why determining the surface properties in Langmuir monolayer is important?

Abstract: In this review we discuss about the immobilization of enzymes in Langmuir-Blodgett films in order to determine the catalytic properties of these biomacromolecules when adsorbed on solid supports. Usually, the conformation of enzymes depends on the environmental conditions imposed to them, including the chemical composition of the matrix, and the morphology and thickness of the film. In this review, we show an outline of manuscripts that report the immobilization of enzymes as LB films since the 1980's, and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Caseli et al. reported a condensed state compressibility modulus of 25.1 mN/m for an L–B film of alkaline phosphatase, , and De Zotti et al , reported a maximum compressibility modulus of 40 mN/m for an L–B film of a peptide, similar to that which we observe. The low-compressibility modulus has been associated with possible conformational changes within the L–B film or eruption/desorption of the peptide at the interphase …”
Section: Resultssupporting
confidence: 88%
“…Caseli et al. reported a condensed state compressibility modulus of 25.1 mN/m for an L–B film of alkaline phosphatase, , and De Zotti et al , reported a maximum compressibility modulus of 40 mN/m for an L–B film of a peptide, similar to that which we observe. The low-compressibility modulus has been associated with possible conformational changes within the L–B film or eruption/desorption of the peptide at the interphase …”
Section: Resultssupporting
confidence: 88%
“…Possarle et al [91] managed to insert carbon nanotubes (CNT) in Langmuir-Blodgett (LB) films of stearic acid (SA), which work as supports for ASNase confinement. The LB technique enables the preparation of ultrathin layers, whose bioinspired support provided by the lipid at air-water interfaces is useful for confinement of enzymes since it allows them to maintain its secondary and tertiary structures [141,142]. After 30 days, the SA-ASNase-CNT monolayer and SA-ASNase In recent years, calcium alginate has stood out as a confinement support material due to its physicochemical features in gel form, essential in the entrapped biologically active material reactions outcome [133].…”
Section: Asnase Confinement By Entrapmentmentioning
confidence: 99%
“…The incorporation of enzymes in solid films using casting, spin-coating, electrodeposition and methods providing organized molecular architectures, e.g., Langmuir-Blodgett (LB) (Blodgett 1935) and layer-by-layer (LbL) (Decher et al 1992), is useful for various applications, including biosensing (Crespilho et al 2006, Leontidis 2016, Moriizumi 1988. Of particular relevance is the LB immobilization of proteins in lipid matrices (Carralero Sanz et al 2005, Vidal et al 2006, which offer a suitable environment for the proteins to retain their activity (Caseli 2018).…”
Section: Introductionmentioning
confidence: 99%